Institutional, Ideological, and Interactional Constraints: The Case of Sexual Abuse in White Evangelical Settings. Issue 3 (19th June 2022) - McKinzie, Ashleigh E.; Richards, Patricia
Abstract : Drawing on 32 interviews with survivors, we examine sexual abuse in white evangelical contexts as a point of intervention in feminist debates over agency. In recent decades, scholars have tended to focus on how women in gender‐traditional religions exercise agency via submission and piety. We argue that the case of abuse points to the limits of agency as a lens to understand women and girls' experiences, and theorize ideological, institutional, and interactional constraints to clarify how evangelical settings may hinder addressing abuse. We explore how these constraints operate within purity culture, which undergirds much of evangelicalism. Purity culture holds women/girls responsible for men/boys' sexuality and lust, restricts access to the language and resources for survivors to identify and cope with abuse, and blames those who try to address it. This analysis has important implications for other settings characterized by the interplay of agency and constraint.